(untitled) (International Journal of Food and Nutritional Sciences, 2022)
CVD being the primary cause of death in India, as well as other metabolic illnesses, there is an immediate need to establish tactics to combat it. Despite the great variety of factors that contribute to CVD, incorrect, unhealthy, and contaminated oil consumption plays a critical part in its progression. Virgin coconut oil (VCO) is highly valued oil with numerous health benefits is demanding research into the adoption of simple and convenient extraction procedures and their acceptability for consumption. The quality indices evaluation revealed that IV of VCO extracted from conventional method was higher (4.38±3.31) whereas SV was found higher for hot method (284.42±4.07). The more FFA value was observed in hot extraction method (0.38±1.02). The functional component of lauric acid in VCO from conventional method (50.17±0.07) was close to the upper limits of reference values and whereas when compared with other oils, the VCO had highest lauric acid than CO and ghee. Moreover the traditional product of millet laddu prepared by using VCO had highest acceptability scores (7.50±0.02) as compared with ghee and CO. Hence we recommend that VCO as a white ghee and can be replaced with normal ghee and also be considered as a general prophylactic against CVD as it has lauric acid and its derivatives.